Mind the gap?: Estimating the effects of postponing higher education - Bertil Holmlund; Qian Liu; Oskar Nordström Skans (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper estimates the effects on earnings of gap years between high school and university enrollment. The effect is estimated by means of standard earnings functions augmented to account for gap years and a rich set of control variables using administrative Swedish data. We find that postponement of higher education is associated with a persistent and non-trivial earnings penalty. The main source of the persistent penalty appears to be the loss of work experience after studies. The reduction of lifetime earnings associated with two years postponement of higher education amounts to 40-50 percent of annual earnings at age 40.
Keywords: I23; J24; J31; 330; Bildungsökonomik; Bildungsverhalten; Zeitpräferenz; Bildungsertrag; Studium; Schweden